Therapeutic Role and Ligands of Medium- to Long-Chain Fatty Acid Receptors - Hara, Takafumi; Ichimura, Atsuhiko; Hirasawa, Akira (Frontiers in Endocrinology, 2014)
Medium- and long-chain free fatty acids (FFAs) are energy source for whole body and biological metabolites and components. In these decades, some research groups have reported that the biological functions of medium- to long-chain FFAs are exerted through G-protein coupled receptor designated free fatty acid receptor (FFAR). As the medium- to long-chain FFAs-activated FFARs, FFA1 and FFA4 are reported to be expressed widely in whole body and regulate various physiological processes. FFA1 expressed in pancreatic β-cells has been shown to be involved in insulin secretion. FFA4 expressed in intestine, adipocytes, and macrophages has been shown to be involved in incretin secretion, differentiation, and anti-inflammatory effect, respectively. These physiological functions have been focused on the treatment of metabolic disorders. In addition, these receptors have been also reported to be expressed in several other tissues such as intestine for FFA1, and tongue and stomach for FFA4. The recent functional studies indicated that they also contributed to energy homeostasis. Further, the number of synthetic compounds of FFA1 and FFA4 strongly promoted the physiological characterization of the receptors and their own therapeutic utility. In this article, we will discuss the recent progress regarding the therapeutic potential of these receptors and its ligands.